Critique of the Institutional Design of the National Economic Prosecutor’s Office: Organ of the Administration or Autonomous Prosecutor? - Serrano Herrera, Carolina Andrea (Revista de Derecho Público, 2022)
Collusion prosecution is a more recent phenomenon than criminal prosecution or administrative sanctions. Around the world, prosecutors’ offices have been given investigative powers in accordance with Criminal Law or Administrative Law. Chile has the National Economic Prosecutor’s Office, whose institutional design borrows elements from both legal regimes, which creates problems for the protection of people’s fundamental rights, especially because of their intrusive investigative powers.